2014
DOI: 10.1021/es503512v
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Nonequilibrium Adsorption of MIB and Sulfamethoxazole by Powdered Activated Carbon and the Role of Dissolved Organic Matter Competition

Abstract: This study demonstrates that the ideal adsorbed solution theory−equivalent background compound (IAST−EBC) as a stand-alone model can simulate and predict the powdered activated carbon (PAC) adsorption of organic micropollutants found in drinking water sources in the presence of background dissolved organic matter (DOM) under nonequilibrium conditions. The IAST−EBC represents the DOM competitive effect as an equivalent background compound (EBC). When adsorbing 2-methylisoborneol (MIB) with PAC, the EBC initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 33 publications
0
33
0
2
Order By: Relevance
“…The validity of this simplified approach has been confirmed for various micropollutants at concentrations ranging from 50 to 200 mg/L in complex wastewater matrices (Kovalova et al, 2013a;Shimabuku et al, 2014;Zoschke et al, 2011). The derivation of eqn.…”
Section: Adsorption Equilibrium In Wastewatermentioning
confidence: 74%
See 1 more Smart Citation
“…The validity of this simplified approach has been confirmed for various micropollutants at concentrations ranging from 50 to 200 mg/L in complex wastewater matrices (Kovalova et al, 2013a;Shimabuku et al, 2014;Zoschke et al, 2011). The derivation of eqn.…”
Section: Adsorption Equilibrium In Wastewatermentioning
confidence: 74%
“…LC-OCD analysis of the wastewater used in this work revealed that, compared to typical surface water, the wastewater matrix contained a relatively large fraction of biopolymers (19%, very high MW (>20 kDa) hydrophilic compounds), but also a significant fraction of low MW neutral compounds (MW < 350 Da, 17.3%) that could compete for adsorption sites with the targeted micropollutants. Correspondingly, recent work showed that the fraction of organic matter competing with MIB and sulfamethoxazole for adsorption sites on PAC was significantly higher in wastewater impacted waters than in non-wastewater impacted surface waters (Shimabuku et al, 2014). A larger fraction of competing EfOM should impact both PAC and SPAC, assuming both the micropollutants and the competing EfOM adsorb to internal pores.…”
Section: Influence Of Effluent Organic Mattermentioning
confidence: 97%
“…The procedure combines the mass balance equations for the adsorbate in the liquid/solid phase system of the solution/adsorbent with equations from the Ideal Adsorbed Solution Theory (IAST) for two solutes of which one is the respective OMP under consideration and the other is a fictive component (the EBC) that accounts for the observed adsorption competition with the considered OMP (Shimabuku et al, 2014;Worch, 2012). For more information on the mathematical modeling procedure we refer to a previous publication (Zietzschmann et al, 2014c).…”
Section: Modelingmentioning
confidence: 99%
“…However, also non-equilibrium adsorption data (i.e. liquid and solid phase concentrations are still changing) can be modeled with the EBCM because of the fictive character of the EBC whose Freundlich parameters are usually fitted to experimental data during backmodeling (Shimabuku et al, 2014;Zietzschmann et al, 2015a;Zoschke et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Another approach was to relate the fitted initial EBC concentration c 0,EBC (non-equilibrium conditions), divided by the DOC of several surface waters to the fluorescence index (FI, ratio of emission intensities at 520 nme470 nm at an excitation at 370 nm) of these waters as higher FI indicated higher BOM competitiveness against OMP adsorption (Shimabuku et al, 2014). Other studies used the EBCM on waters whose BOM was artificially altered (membrane filtration, ozonation), and related increased BOM competitiveness to smaller molecular sizes (Zietzschmann et al, 2014b) or aromaticity and polarity (Zietzschmann et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%